Citrulline‐Specific Th1 Cells Are Increased in Rheumatoid Arthritis and Their Frequency Is Influenced by Disease Duration and Therapy - James, Eddie A.; Rieck, Mary; Pieper, Jennifer; Gebe, John A.; Yue, Betty B.; Tatum, Megan; Peda, Melissa; Sandin, Charlotta; Klareskog, Lars; Malmström, Vivianne; Buckner, Jane H. (Arthritis & rheumatology (Hoboken, N.J.), 2014)
Objective Rheumatoid arthritis (RA) is thought to be a T cell–mediated disease, based on its strong association with HLA class II alleles, clinical responsiveness to T cell–directed therapies, and the presence of CD4+ T cells in rheumatoid joints. The presence of anti–citrullinated protein antibodies (ACPAs) in RA serum and the association of these antibodies with HLA–DR4 alleles implicate citrulline‐specific autoreactive T cells in the development and progression of RA. The goal of this study was to determine the characteristics and specificity of autoreactive T cell responses in RA. Methods We developed a panel of HLA–DRB1*04:01 tetramers, selecting citrullinated peptides from synovial antigens and verifying their immunogenicity in DRB1*04:01‐transgenic mice. Seven tetramers were used to examine the ex vivo frequency and surface phenotype of citrulline‐specific (Cit‐specific) T cells in patients with RA and healthy subjects with DRB1*04:01 haplotypes, using a magnetic enrichment procedure. Results Cit‐specific T cells were detectable in peripheral blood samples from both healthy subjects and RA patients. In comparison to healthy subjects, RA patients had significantly higher frequencies of Cit‐specific T cells, and a greater proportion of these cells displayed a Th1 memory phenotype. Among RA patients, the frequency of Cit‐specific T cells was highest within the first 5 years after diagnosis of RA and was decreased in patients taking biologic agents, irrespective of disease duration. Conclusion These findings link the presence of ACPAs in RA with Th1 cells specific for citrullinated epitopes and provide tools for disease‐specific immunomonitoring of autoreactive T cells.